Características individuais, fatores comportamentais e ambientais associados a eventos críticos para a segurança de ciclistas universitários - Truchym, Talita Chrystoval (2019)
AIM: To analyze the association between individual characteristics, behavioral and environmental factors and safety-critical events during cycling. METHODOLOGY: Quantitative, observational study of longitudinal design. The study sample was intentionally selected, participants were recruited from previously selected bike racks. Participants were provided with a camera and portable Global Positioning System (GPS) and commute journals to record all bicycle journeys for seven consecutive days. In addition, the participant was asked to indicate in the travel log the safety-critical events (ECS), self-reported situations, based on the perception of insecurity or discomfort while riding the bicycle that represented a step prior to an accident. The ECS indicated by the participants were validated by the author. Routes filmed with valid ECS were fractionated over 30-second periods. These periods were considered the unit of analysis for identifying associated factors. To identify the associated factors, a case control design was used. A comparison was made between three 30-second periods without ECS (controls) and a 30-second period with ECS (case). To evaluate the behavioral and environmental variables in the 30-second periods an instrument was developed. The instrument had its reproducibility tested by Kappa index and Intraclass Correlation Coefficient. Reproducibility values were considered adequate (> 0.70). Descriptive analyzes and chi-square test (χ2) were performed to verify the association between the variables. The software SPSS version 20.0 was used to perform data analysis (5%). RESULTS: 23 college students participated in the study data analysis. In total, 76 ECS were indicated and 54 were considered valid. Most ECS were considered conflicts (98.1%), with drivers (82.4%), driving ahead (71.4%) or performing conversion on the left (16.7%). The only collision was a pedestrian interaction. The overall incidence density was 1.69 ECS / h. It was higher among men, in the largest age group, among those with income between 1 and 3 times the minimum wage, with frequency of use 3x / week, who do not use headphones, when traveling outside the home-university-work axis, in lower average speeds and maximum speeds between 26.67 and 32.84 km / h. The presence of vehicles parked on both sides of the road was positively associated with the presence of ECS. Pedaling the shared sidewalk, pedaling in regions with traffic control and being stationary were inversely associated with the presence of ECS. CONCLUSION: This study can assist public managers in the implementation of policies that help the safety of all road users and can also help physical education professionals in the dissemination of safer use of bicycle while traveling.